THE METHODS OF DEVELOPING CREATIVITY IN STUDENTS IN THE FIELD OF PEDAGOGY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article discusses the importance of developing creativity in students within the field of pedagogy. It examines effective methods and innovative teaching approaches that enhance creative thinking, problem-solving, and self-expression among learners. The paper also highlights the views of both Uzbek and foreign scholars on creativity and its role in modern education.